ANTIMONIATO DE MEGLUMINA (GLUCANTIME®) CAUSA DANOS AO DNA POR ESTRESSE OXIDATIVO E INDUZ SUPEREXPRESSÃO DE GENES ENVOLVIDOS NA DEFESA ANTIOXIDANTE E REPARO DO DNA. - MOREIRA, Vanessa Ribeiro (2017)
Leishmaniasis is a neglected disease caused by more than 20 species of parasites of the Leishmania genus. Pentavalent antimonials are the drugs commonly used for the treatment of leishmaniasi and among then Glucantime® is the first choice drug recommended by the World Health Organization. Its toxic effects are well known, including as genetic damage inducing. However, the mechanism of its genotoxic effect has not been elucidated yet. Given this, we investigated the mechanism by which Glucantime® causes damage to DNA in BALB/c mice infected with Leishmania (Leishmania) infantum, treated with 20mg/kg/day during 20 days. Damage to DNA have been assessed by the comet assay using peripheral blood leukocytes and for assessment of oxidative damage, the comet assay was followed by treatment with the enzymes formamidopyrimidine-DNA-glycosylase (Fpg) and endonuclease III (ENDO III), which recognize and remove oxidized purines and pyrimidines of DNA. The mutagenic potential of the drug was investigated by the micronucleus test in bone marrow cells. The consequences of the oxidative process were measured by the activity of the enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx). In addition, we evaluated the expression of genes related to antioxidante defense (GSS, GSTP1, GPx1, SOD1, SOD2 and CAT) and to the DNA repair system (OGG1 and MTH1). Our data demonstrated that Glucantime® causes damage to DNA in mammalian cells by oxidating the nitrogenous bases. The increased frequency of micronucleated cells in animals treated with antileishmanial revealed that the genomic instability was fixed in mutations. In addition, Glucantime® induced overexpression of genes related to the antioxidant defense, as well as the genes OGG1 and MTH1, that work in the DNA repair mechanism of damage caused by oxidation of nitrogen bases. Our data also revealed that infection by L. infantum and the treatment with antimonial significantly increased the enzymatic activity in the SOD-CAT axis, while the SOD-GPx axis was inhibited, probably by the depletion of glutathione. Thus, our data suggests that the antimonial pledges to GPx leading to saturation of the antioxidant system and causes damage to DNA through oxidative stress. These findings were supported by the reduction of genetic damage thought a treatment combined with ascorbic acid, a potent antioxidant. At last, we demonstrated that the stressfull effect of Glucantime® triggers a molecular response in mammalian cells, positively modulating the expression. Of genes related to DNA repair and antioxidant defense.